2023
DOI: 10.1029/2022ja031125
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Differential Deep Penetration of Energetic Electrons and Protons into the Low L Region (L < 4)

Abstract: Deep penetration of energetic electrons (10s–100s of keV) to low L‐shells (L < 4), as an important source of inner belt electrons, is commonly observed during geomagnetically active times. However, such deep penetration is not observed as frequently for similar energy protons, for which underlying mechanisms are not fully understood. To study their differential deep penetration, we conducted a statistical analysis using phase space densities (PSDs) of µ = 10–50 MeV/G, K = 0.14 G1/2Re electrons and protons from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Figure 2 demonstrates variations of radiation belt electrons across a wide range in energy: 0.25–6 MeV and L : 1–7. Some of these features have been reported before in different formats, such as energy‐dependent deep penetration of electrons in which very few multi‐MeV electrons were observed below L = 2.6 (Baker et al., 2014; Hogan et al., 2021; X. Li, Baker, et al., 2017; X. Li et al., 1993, 2021; O’Brien et al., 2023; Zhao & Li, 2013a) while less energetic (∼1 MeV) electrons are often seen penetrating into the slot region and sometimes even into the inner belt ( L < 2) (Baker et al., 2004; Claudepierre et al., 2019; Kim et al., 2016; Zhao & Li, 2013b; Zhao et al., 2023; Zheng et al., 2006). Dispersionless injections have mostly been studied using observations near the equatorial plane (Gabrielse et al., 2016; X. Li et al., 1998; Sarris et al., 2002).…”
Section: Measurement Results and Discussionmentioning
confidence: 99%
“…Figure 2 demonstrates variations of radiation belt electrons across a wide range in energy: 0.25–6 MeV and L : 1–7. Some of these features have been reported before in different formats, such as energy‐dependent deep penetration of electrons in which very few multi‐MeV electrons were observed below L = 2.6 (Baker et al., 2014; Hogan et al., 2021; X. Li, Baker, et al., 2017; X. Li et al., 1993, 2021; O’Brien et al., 2023; Zhao & Li, 2013a) while less energetic (∼1 MeV) electrons are often seen penetrating into the slot region and sometimes even into the inner belt ( L < 2) (Baker et al., 2004; Claudepierre et al., 2019; Kim et al., 2016; Zhao & Li, 2013b; Zhao et al., 2023; Zheng et al., 2006). Dispersionless injections have mostly been studied using observations near the equatorial plane (Gabrielse et al., 2016; X. Li et al., 1998; Sarris et al., 2002).…”
Section: Measurement Results and Discussionmentioning
confidence: 99%
“…Zhao et al. (2013) reported that 100's keV electron flux would enhance in the inner belt even during moderate storms. Selesnick et al.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the discrepant characteristic of energy dependent increases of flux, we can conclude that the #4 flux increases are related to electron penetration during a geomagnetic storm and the #5 flux increases are produced by NWC transmitter signals. It is evident that storms are just moderate for #1 and #4 flux increases, with minimum Dst ≈ −50 nT, which suggests that strong injections of 100's keV electrons in the inner belt can happen during moderate or weak storms (Zhao et al., 2023; Zhao & Li, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations